REKAYASA PERANGKAT LUNAK DENGAN MODEL UNIFIED PROCESS STUDI KASUS: SISTEM INFORMASI JOURNAL - Akil, Ibnu (LPPM Universitas Nusa Mandiri, 2016)
In the era of object oriented programming, the analysis models of structured approaches is start to be left behind, because it is no longer relevan with object-oriented paradigm. Nowadays who become the standard of analysis and design of object-oriented system is Unified Modeling Language (UML). However UML is just notations, it doesn’t provide a framework to work in software engineering. The Unified Proces which proposed by Rumbaugh and friends, is a framework for object-oriented software engineering.